Prognosis of Placental Insufficiency in Pregnant Women Treated for Coronavirus (Eurasian Medical Research Periodical, 2023)
The aim of the scientists' research is to optimize the treatment of pregnant women with a moderate form of a new coronavirus infection by including a sorbent in complex therapy